The water–energy nexus in irrigated agriculture in South Asia: Critical hotspots of irrigation water use, related energy application, and greenhouse gas emissions for wheat, rice, sugarcane, and cotton in Pakistan - Siyal, Abdul Wahab; Gerbens-Leenes, P. Winnie (Frontiers in Water, 2022)
Asia has a large water scarcity problem, especially countries depending on irrigation, limiting agricultural production and increasing food insecurity. When water becomes scarce, it needs conveyance over longer distances or pumping from deeper groundwater stocks, requiring pumping energy, often fossil energy, emitting greenhouse gasses. This causes a trade-off between irrigation water supply and fossil energy use contributing to global warming. This research focusses on the water-energy-food nexus in irrigated agriculture to improve resource management. It uses Pakistan as its case study area and assesses water consumption, energy (EFs) and carbon footprints (CFs) associated with irrigation water supply for the major crops (wheat,rice, sugarcane and cotton) per district. The research indentifies unfavorable hotspots and favorable areas from a water and energy perspective. Drivers determining water consumption, EFs and CFs related to irrigation water supply show spatial and temporal differences and include: crop types, temporal crop water requirements, fractions of gravity-fed and pumped water, groundwater tables and energy sources (diesel, electric, solar). In Pakistan, annual irrigation supply requires 103 PJ of energy generating a CF of 11 109 kg CO2 (6% of the national CF). Diesel pumps pumping shallow groundwater contribute most (73%), followed by electric pumps pumping deep groundwater. Energy for surface water pumping is negligible. Wheat contributes 31% to the EF, cotton 27%, sugarcane and rice 21% each. CFs are also dominated by wheat (32%) and cotton (31%), followed by rice and sugar cane (19% each). Ten hotspot districts contribute 42% to the EF of the major crops and increased by 21% in fourteen years. Wheat and cotton in Punjab, and rice and cotton in Sindh are most energy-intensive. EFs range between 3,500 to 5,000 TJ per district, with some districts in Punjab, the most important agricultural province, using even more. Large differences occur among EFs per unit of irrigation water, ranging between 7 and 2,260 KJ/m3, CFs between one and 444 g CO2 /m3. The identification of hotspots may contribute to measures to minimize water consumption, EFs and CFs for agriculture in Pakistan. Other countries that also rely on irrigation could apply methods applied here to identify hotspots.